Genetic pattern and penetrance of polycystic kidney disease in the Western region of Iraq - Louay Mohammed Alani (مجلة جامعة الانبار للعلوم الصرفة, 2012)
The aims of this study are to identify the genetic pattern, estimation of gene frequency, penterance, prevalence of PKD, and to furnish an appropriate plan for genetic counselling specific for these families under investigation. A total of 41 families reside in the western region of Iraq were included in this study. This study showed that PKD is inherited as an autosomal dominant disease due to the defects in PKD1 gene. Gene frequency was 0.003 and 0.997 for p and q respectively. Genotype frequency was 0.000009, 0.005982 and 0.994009 for p2, 2pq and p2, respectively. The prevalence of the disease is 3.7/1000. The mutation was originated outside this family. The individual numberthree from parent generation (Generation- I-3) who is the patient which brought this defected gene to all of her descendants. Gene flow of the defected gene into these families increased the frequency of p gradually.